Impact of sickness induced by centrifugation on tilt perception - Taylor L. Lonner; Caroline R. Austin; Joanna S. Blake; Parinie Gupta; Jason M. Katz; Aadhit R. Gopinath; Torin K. Clark (Frontiers in Neurology)
IntroductionSickness induced by centrifugation (SIC) is an analog for sensorimotor impairment and motion sickness associated with gravity transitions experienced by astronauts. The paradigm involves sustained centrifugation to create a static Gx (into the eyes) hypergravity exposure, following which vestibular-mediated functions, such as balance and eye movements, have been found to be degraded or altered. Furthermore, astronauts who were more prone to space motion sickness were also more susceptible to motion sickness following SIC. However, the vestibular and perceptual processing alterations induced by SIC remain poorly understood as human tilt perception following SIC has not yet been quantified.MethodsWe assessed the impact of SIC on the perception of self-roll tilt and pitch tilt in a total of twenty healthy subjects. On one testing day, the subjects were exposed to the SIC analog, wherein they underwent an hour of 2Gx centrifugation. Afterwards, they reported tilt perception while seated in the dark during a variety of static and dynamic tilt and translation motion profiles, either in a roll tilt or pitch tilt configuration. These results were compared to tilt perception following a baseline condition on a separate testing day where subjects laid supine for an hour.ResultsWhen compared to the baseline condition, SIC exposure resulted in a significant underestimation of −33.2% in the pitch tilt angle (t(60) = −4.39, p < 0.0005), but no effect in roll (mean underestimation of −7.5%, t(60) = −0.68, p = 0.50).DiscussionWe discuss the implications of these vestibular perceptual effects of SIC as an analog for spaceflight-associated spatial disorientation.